Suspended stable powder fluid loss agent and preparation method thereof

By introducing layered silicate clay and modification additives into high-temperature cement slurry, the composite particles and thixotropic mesh structure is formed, the problem of poor settlement stability of high-temperature cement slurry is solved, and the water loss of cementing API is controlled below 240℃ is achieved, which improves the safety and quality of cementing operations.

CN119662228APending Publication Date: 2025-03-21CNPC BOHAI DRILLING ENG +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311213638.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-20
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing high-temperature cement slurry system is difficult to guarantee settlement stability when it is above 200°C, which can easily cause bridge blockage or trough breakage. The density difference of the cement slurry columns affects the uniformity of cement stone and the later strength development, endangering the safety of cementing operations and reducing cementing quality.

Method used

A suspension-stable powder water-reducing agent is used, which is a composite of a polymer system and a modification additive. By introducing layered silicate clay and a modification additive into the polymer system, a composite particle and a thixotropic mesh structure is formed to improve the settlement stability of the cement slurry.

Benefits of technology

The API water loss in ultra-high temperature cement slurry below 240℃ is achieved to control the API water loss within 40mL, ensuring the settlement stability of the cement slurry and improving the safety and quality of cementing operations.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a suspension stable type powder fluid loss agent and a preparation method thereof. The fluid loss agent is a compound of a polymer system and a performance additive, the polymer system is formed by copolymerizing a monomer A, a monomer B and a monomer C in a reaction system containing layered silicate clay; the monomer A is 2-acrylamido-2-sodium methyl propanesulfonate, sodium p-styrenesulfonate or 3-allyloxy-2-hydroxy-1-sodium propanesulfonate, and the monomer B is a monomer C; the monomer B is 4-acryloyl morpholine, N, N-dimethylacrylamide or N, N-diethyl acrylamide; the monomer C is methacrylic acid, maleic acid, butenoic acid or fumaric acid; the modification auxiliary agents comprise a modification auxiliary agent A, a modification auxiliary agent B and a modification auxiliary agent C; the performance additive A is welan gum and / or dimer gum; the performance additive B is sulfonated phenolic resin and / or hectorite powder, and the performance additive C is at least one of limestone powder, dolomite powder and pickled quartz sand; the preparation method of the fluid loss agent is simple, the sedimentation stability of cement paste is effectively improved, the fluid loss agent can resist the temperature of 240 DEG C, and the API fluid loss is small.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oil and gas well cementing admixtures, and in particular to a suspension stable powder fluid loss additive and a preparation method thereof. Background Art

[0002] Cementing slurry technology has made great progress. At present, high-temperature cement slurry systems within 180°C are relatively mature. However, the sedimentation stability of cement slurry systems above 200°C is not easy to guarantee. Free liquid and particle sedimentation will occur during the cementing process, which can easily cause bridging or channeling. In addition, there are density differences in cement slurry columns at different locations underground, which will affect the uniformity of cement stone and the subsequent strength development, endangering the safety of cementing operations and reducing cementing quality.

[0003] 2-Acrylamide-2-methylpropanesulfonic acid (AMPS) copolymer fluid loss reducers are widely used in high-temperature cementing due to their good heat and salt resistance. However, the presence of anionic groups such as sulfonic acid and carboxyl groups in such copolymers makes them have the disadvantage of strong high-temperature dispersibility, which has an adverse effect on the sedimentation stability of cement slurry. In addition, liquid fluid loss reducer products have a short shelf life when used in hot weather, and are prone to mildew or degradation, which seriously affects the comprehensive performance of the product; when used in cold winter weather, they are prone to increase viscosity or even loss of fluidity, affecting the normal use of the product. Therefore, it is of great significance to develop a suspension-stable powder fluid loss reducer. Summary of the invention

[0004] The purpose of the present invention is to provide a suspension-stable powder fluid loss reducer which can be used at a temperature of up to 240°C and can control the API water loss of ultra-high temperature cement slurry within 40 mL at 240°C.

[0005] Another object of the present invention is to provide a method for preparing the above-mentioned suspension-stable powder fluid loss additive.

[0006] To this end, the technical solution of the present invention is as follows:

[0007] A suspension stable powder fluid loss additive, which is a composite of a polymer system and a modification aid; wherein the polymer system is formed by copolymerizing 60% to 80% by mass of a monomer A, 15% to 30% by mass of a monomer B and 5% to 10% by mass of a monomer C in a reaction system containing layered silicate clay; the monomer A is sodium 2-acrylamido-2-methylpropanesulfonate, sodium p-styrenesulfonate or sodium 3-allyloxy-2-hydroxy-1-propanesulfonate; the monomer B is 4-acryloylmorpholine, N,N-dimethoxy-1-propanesulfonate, Methacrylamide or N,N-diethylacrylamide; monomer C is methacrylic acid, maleic acid, crotonic acid or fumaric acid; the amount of layered silicate clay added is 10% to 20% of the total weight of monomer A, monomer B and monomer C; the modification aid is a mixture of modification aid A, modification aid B and modification aid C; modification aid A is at least one of Wenlun rubber and Dingyou rubber; modification aid B is at least one of sulfonated phenolic resin and lithium soapstone powder, and modification aid C is at least one of limestone powder, dolomite powder and acid-washed quartz sand.

[0008] In the suspension-stable powder fluid loss additive, the purpose of introducing layered silicate clay into the copolymer system is to make the layered silicate clay adsorb polymers to form composite particles through electrostatic adsorption and inter-ionic complexation, so that the composite particles also have the thixotropic network structure of layered silicate clay, and then while the polymer is adsorbed on the surface of cement particles as a bridge, the composite particles support cement particles through the thixotropic network structure to play a role in suspension stability; and the introduction of modified additives into the copolymer system is to utilize the compounding of different modified additives to improve the high-temperature suspension stability effect of the fluid loss additive by improving the thixotropic viscosity-increasing ability on the one hand, and on the other hand, it is conducive to the accuracy of the dosage during the adjustment period, thereby ensuring the stability of the suspension stability performance of the prepared fluid loss additive system.

[0009] Preferably, the layered silicate clay is at least one of halloysite clay, chlorite clay, montmorillonite clay and illite clay.

[0010] Preferably, the weight ratio of the modifying aid A, the modifying aid B and the modifying aid C is 2:(1-2):(4-5).

[0011] Preferably, the weight ratio of the polymer system powder to the modification aid is 2:8.

[0012] A method for preparing the above-mentioned suspension stable powder fluid loss additive comprises the following steps:

[0013] S1, dissolving 10 to 30 parts of the comonomer in 70 to 90 parts of water and stirring evenly, then adding 10% to 20% of the total weight of the comonomer layered silicate clay and 0.1% to 1% of the initiator ammonium persulfate, reacting at 60° C. to 85° C. for 2 h to 5 h to obtain a polymer system;

[0014] S2. Dry the polymer system and crush it into powder, mix the modified additive and the polymer system evenly to obtain a suspended stable powder fluid loss additive.

[0015] Compared with the prior art, the suspension-stable powdered fluid loss additive is prepared by introducing layered silicate clay into a polymer system and compounding the polymer system with a modified additive to achieve synergistic enhancement, so as to offset and improve the high-temperature dispersibility of the fluid loss additive and play a role in suspension stabilization. The applicable temperature can reach 240°C, and the API water loss of ultra-high temperature cement slurry at 240°C can be controlled within 40mL, and the sedimentation stability is good. DETAILED DESCRIPTION

[0016] The present invention will be further described below in conjunction with specific examples, but the following examples are by no means intended to limit the present invention in any way.

[0017] Example 1

[0018] A suspension stable powder fluid loss additive is prepared by the following method:

[0019] S1, dissolving 16 g of sodium 2-acrylamido-2-methylpropanesulfonate, 3 g of 4-acryloylmorpholine and 1 g of maleic acid in 80 g of water and stirring evenly, then adding 4 g of halloysite clay and 0.11 g of initiator ammonium persulfate, reacting at 72.5° C. for 3.5 h to obtain a polymer system;

[0020] S2. Dry the polymer system and crush it into powder, and mix the polymer system powder, dimethoate, sulfonated phenolic resin and acid-washed quartz sand in a weight ratio of 2:2:1:5 to obtain a suspended stable powder fluid loss additive.

[0021] Example 2

[0022] A suspension stable powder fluid loss additive is prepared by the following method:

[0023] S1, dissolving 18g of sodium p-styrene sulfonate, 9g of N,N-dimethylacrylamide and 3g of methacrylic acid in 70g of water and stirring evenly, then adding 2g of montmorillonite clay and 1g of chlorite clay, and 0.03g of initiator ammonium persulfate, reacting at 60°C for 5h to obtain a polymer system;

[0024] S2. Dry the polymer system and crush it into powder, and mix the polymer system powder, Wenlun rubber, lithium laponite and limestone powder in a weight ratio of 2:2:2:4 to obtain a suspended stable powder fluid loss additive.

[0025] Example 3

[0026] A suspension stable powder fluid loss additive is prepared by the following method:

[0027] S1, dissolving 7 g of sodium 3-allyloxy-2-hydroxy-1-propanesulfonate, 2.25 g of N,N-diethylacrylamide, 0.5 g of maleic acid and 0.25 g of fumaric acid in 90 g of water and stirring evenly, then adding 1.5 g of illite clay and 0.1 g of initiator ammonium persulfate, reacting at 85° C. for 2 h to obtain a polymer system;

[0028] S2. Dry the polymer system and crush it into powder, and mix the polymer system powder, Wenlun rubber, sulfonated phenolic resin and dolomite powder in a weight ratio of 2:2:1:5 to obtain a suspended stable powder fluid loss additive.

[0029] Example 4

[0030] A suspension stable powder fluid loss additive is prepared by the following method:

[0031] S1, dissolving 13.5 g of sodium 2-acrylamido-2-methylpropanesulfonate, 3.6 g of 4-acryloylmorpholine, and 0.9 g of maleic acid in 92 g of water and stirring evenly, then adding 3.6 g of halloysite clay and 0.108 g of initiator ammonium persulfate, reacting at 75° C. for 3 h to obtain a polymer system;

[0032] S2. Dry and crush the polymer system into powder, and mix the polymer system powder, dimethoate, sulfonated phenolic resin, dolomite powder and limestone powder in a weight ratio of 2:2:1:2:3 to obtain a suspended stable powder fluid loss additive.

[0033] Comparative Example 1

[0034] A fluid loss reducer is prepared by the following method:

[0035] 16 g of sodium 2-acrylamido-2-methylpropanesulfonate, 3 g of 4-acryloylmorpholine and 1 g of maleic acid were weighed and dissolved in 80 g of water and stirred evenly, 0.11 g of initiator ammonium persulfate was added, and the mixture was reacted at 72.5° C. for 3.5 h to obtain a high-temperature fluid loss reducer for oil well cement.

[0036] Comparative Example 2

[0037] A fluid loss reducer is prepared by the following method:

[0038] 16 g of sodium 2-acrylamido-2-methylpropanesulfonate, 3 g of 4-acryloylmorpholine and 1 g of maleic acid were dissolved in 80 g of water and stirred evenly, and then 4 g of halloysite clay and 0.11 g of initiator ammonium persulfate were added, and the mixture was reacted at 72.5° C. for 3.5 h to obtain a high-temperature fluid loss reducer for oil well cement.

[0039] Performance Test:

[0040] According to the petroleum and natural gas industry standard SY / T 5504.2-2013 "Evaluation Methods for Oil Well Cement Admixtures Part 2: Fluid Loss Additives" and the national standard GB / T 19139-2012 "Test Methods for Oil Well Cement", the fluid loss additives prepared in Examples 1 to 4 and Comparative Example 1 were evaluated for cement slurry performance.

[0041] Prepare the test cement slurry, the cement slurry formula is G-grade oil well cement + 35% quartz sand (BWOC, the same below) + retarder (dosage see Table 1) + fluid loss reducer (dosage see Table 1) + 0.8% dispersant + 48-52% water, and the cement slurry density is controlled to 1.90±0.01g / cm by adjusting the amount of water added 3 The G-grade oil well cement uses the Jiahua G-grade high sulfur-resistant oil well cement produced by Jiahua Special Cement Co., Ltd., the retarder uses the retarder GH-9 produced by Weihui Chemical Co., Ltd., and the dispersant uses the dispersant USZ produced by Weihui Chemical Co., Ltd.

[0042] The cement slurry was placed in a high temperature and high pressure thickener and cured for 30 minutes at different test temperatures and pressures as shown in Table 1. After cooling to 90°C, it was removed, and the residual oil on the upper layer of the slurry was removed and stirred evenly. Then, it was placed in a 90°C water bath for 2 hours to measure the free liquid and sedimentation stability, or placed in a high temperature and high pressure dehydration instrument and heated to the test temperature to evaluate the dehydration performance. The specific test results are shown in Table 1 below.

[0043] Table 1:

[0044]

[0045] In Table 1, “#” represents the mass percentage of cement, and “—” represents that the slurry settles severely during the heating and waiting process in the static water loss instrument, and the accurate water loss cannot be measured.

[0046] It can be seen from the test results in Table 1 that the water loss test results of Examples 1 to 4 show that as the test temperature increases, by appropriately adjusting the amount of water loss reducer in the cement slurry, the API water loss of the cement slurry can be controlled within 40 mL in the temperature range of 150°C to 240°C. The water loss reducer of Comparative Example 1 is composed only of a copolymer system; compared with Examples 1 to 4, the cement slurry prepared by the water loss reducer of Comparative Example 1 settles severely during the temperature rise waiting process in the static water loss instrument, and the accurate water loss cannot be measured; the water loss reducer of Comparative Example 2 is composed only of a copolymer system and layered silicate clay. Compared with Examples 1 to 4, the water loss problem of the cement slurry prepared by the water loss reducer of Comparative Example 2 during the temperature rise process of the 200°C static water loss test is improved, but the cement slurry settles severely during the temperature rise process of the 240°C static water loss test, and the accurate water loss cannot be measured.

[0047] After the cement slurry prepared with the fluid loss reducer of Comparative Example 1 was cured at 200°C and 240°C, the free liquid content of the slurry was ≥0.8% and the sedimentation stability was ≥0.09 g / cm 3 It can be seen that the cement slurry is severely diluted at high temperature, resulting in poor stability; after the cement slurry prepared with the fluid loss agent of Comparative Example 2 is cured at 200°C, the free liquid content of the slurry is reduced compared with Comparative Example 1, and the sedimentation stability is also improved, but after the cement slurry prepared with the fluid loss agent of Comparative Example 2 is cured at 200°C, the free liquid content and sedimentation stability of the slurry are deteriorated due to severe high-temperature dilution, resulting in its applicable temperature can only reach 200°C; and after the cement slurry prepared with the fluid loss agent of Examples 1 to 4 is cured at 200°C and 240°C, the free liquid content of the slurry is ≤0.3%, and the high-temperature sedimentation stability is <0.05g / cm 3 It is explained that the fluid loss reducer of the present application forms composite particles by introducing layered silicate clay in the process of generating the copolymer system, and compounding the composite particles with the modified additive to achieve a synergistic effect, thereby achieving the purpose of significantly improving the problem of poor sedimentation stability of cement slurry caused by the strong side effect of high-temperature dispersion of the copolymer fluid loss reducer. The fluid loss reducer of the present application offsets and improves the high-temperature dispersibility of the fluid loss reducer, has good suspension stability, and is applicable at a temperature of up to 240°C. The API water loss of the cement slurry can be controlled within 40mL, and has a good application prospect.

Claims

1. A suspension-stable powder fluid loss additive, characterized in that: It is a composite of a polymer system and a modification aid; wherein the polymer system is copolymerized by weight fractions of 60% to 80% monomer A, 15% to 30% monomer B and 5% to 10% monomer C in a reaction system containing layered silicate clay; monomer A is sodium 2-acrylamido-2-methylpropanesulfonate, sodium p-styrenesulfonate or sodium 3-allyloxy-2-hydroxy-1-propanesulfonate; monomer B is 4-acryloylmorpholine, N,N-dimethylacrylamide or N,N-diethylacrylamide; monomer C is methacrylic acid, maleic acid, crotonic acid or fumaric acid; the amount of layered silicate clay added is 10% to 20% of the total weight of monomer A, monomer B and monomer C; the modification aid is a mixture of modification aid A, modification aid B and modification aid C; modification aid A is at least one of Wenlun rubber and Dingyou rubber; modification aid B is at least one of sulfonated phenolic resin and lithium soapstone powder, and modification aid C is at least one of limestone powder, dolomite powder and acid-washed quartz sand.

2. The suspension-stable powder fluid loss additive according to claim 1, characterized in that: The layered silicate clay is at least one of halloysite clay, chlorite clay, montmorillonite clay and illite clay.

3. The suspension-stable powder fluid loss additive according to claim 1, characterized in that: The weight ratio of the modification aid A, the modification aid B and the modification aid C is 2:(1-2):(4-5).

4. The suspension-stable powder fluid loss additive according to claim 1, characterized in that: The weight ratio of the polymer system powder to the modification aid is 2:

8.

5. A method for preparing a suspension-stable powder fluid loss additive according to any one of claims 1 to 4, characterized in that: Here are the steps: S1, dissolving 10 to 30 parts of the comonomer in 70 to 90 parts of water and stirring evenly, then adding 10% to 20% of the total weight of the comonomer layered silicate clay and 0.1% to 1% of the initiator ammonium persulfate, reacting at 60° C. to 85° C. for 2 h to 5 h to obtain a polymer system; S2. Dry the polymer system and crush it into powder, mix the modified additive and the polymer system evenly to obtain a suspended stable powder fluid loss additive.